KONTRIBUSI WAKTU DAN PENDAPATAN WANITA PENGRAJIN LIDI DALAM RUMAH TANGGA DI KECAMATAN TUALANG KABUPATEN SIAK (Studi Kasus : Wanita Pengrajin Lidi Kelapa Sawit Desa Tualang Timur) - Bambang Suardi; Rosnita Rosnita; Yulia Andriani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
This research aims to describe the profile of oil palm sticks agroindustry, describe the profile of women crafts in the oil palm sticks industry, find out the time allocation, and the contribution of women palm oil stick craftsmen, and analyze the contribution of women's income from the sticks agroindustry business households in Tualang Timur village, Tualang district Siak regency. The research method used is the census method. The data used are primary data and secondary data. Informants in this study were all members of the women's group of oil palm stick craft in Tualang Timur village Tualang district Siak regency. The results of this research indicate that the largest time allocation for women is on productive activities of 42 hours per week and the smallest time allocation for social activities is 0.85 hours per week. The average acceptance of women as owners as well as craft is Rp. 1,331,400 per month. When viewed from family income, it turns out that the income of the owner's family is greater, where the average income of the owner's family is Rp. 4,856,400 per month. So it can be seen that the contribution of women is 27.41 percent in family income.. Keywords : Contribution of women's time, women's income, oil palm stick crafts